2002
DOI: 10.1139/e01-100
|View full text |Cite
|
Sign up to set email alerts
|

A gravity profile across southern Saganash Lake fault: implications for the origin of the Kapuskasing Structural Zone

Abstract: A high-resolution gravity profile, with station elevations and locations determined by a differential Global Positioning System, shows that the Saganash Lake fault that defines the northwestern boundary of the southern Kapuskasing Structural Zone (KSZ) is southeast dipping and of reverse type. Previous interpretations of a normal fault, caused by crustal collapse following east-verging thrusting along the Ivanhoe Lake fault that forms the southeastern boundary of the KSZ are no longer tenable. Instead, the rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…The Wawa Gneiss Domain is separated from the granulite facies (deep crust) Kapuskasing Structural Zone to the east by a gradational metamorphic contact (Percival, 1983). Shear zones define the most pervasive fabric in the Wawa Gneiss Domain, becoming ubiquitous and defining the regional scale Saganash Lake fault when approaching the Kapuskasing Structural Zone (Moser, 1994; Nitescu & Halls, 2002). The hornblende–biotite gneisses of the Wawa Gneiss Domain enclose metre‐ to decametre‐sized hornblende–plagioclase–clinopyroxene rafts (Figure 2b), which are commonly crosscut by granodiorite dykes and quartz‐monzonite pegmatites (Percival, 1990).…”
Section: Regional Geologymentioning
confidence: 99%
“…The Wawa Gneiss Domain is separated from the granulite facies (deep crust) Kapuskasing Structural Zone to the east by a gradational metamorphic contact (Percival, 1983). Shear zones define the most pervasive fabric in the Wawa Gneiss Domain, becoming ubiquitous and defining the regional scale Saganash Lake fault when approaching the Kapuskasing Structural Zone (Moser, 1994; Nitescu & Halls, 2002). The hornblende–biotite gneisses of the Wawa Gneiss Domain enclose metre‐ to decametre‐sized hornblende–plagioclase–clinopyroxene rafts (Figure 2b), which are commonly crosscut by granodiorite dykes and quartz‐monzonite pegmatites (Percival, 1990).…”
Section: Regional Geologymentioning
confidence: 99%
“…1) is the largest and the most extensively studied. The smaller Swayze greenstone belt is situated in the western part of the Abitibi Subprovince (Figs 1 & 2), where its western limit corresponds to the Kapuskasing structure, a Proterozoic uplift of Archaean high-grade metamorphic rocks corresponding to a crustal-scale thrust or flower structure (Percival 1988;Nitescu & Halls 2002). The Kenogamissi complex, a large crystalline complex composed of multiple plutons of distinctly different ages, straddles the boundary between the Abitibi and Swayze greenstone belts (Fig.…”
Section: Geological Settingmentioning
confidence: 99%
“…For example, Halls and Mound (1998), and Nitescu and Halls (2002) established the faultdeveloping situation in the Kapuskasing structural zone with gravity profile and GPS data. Meng et al (1990), Wang et al (1997), and Yang et al (2015) all found crustal block structures using gravity profile data and so on.…”
Section: Introductionmentioning
confidence: 99%